Genetically Modified Cell Transplantation Through Macroencapsulated Spheroids with Scaffolds to Treat Fabry Disease. (20th December 2021) - Kami, Daisuke; Suzuki, Yosuke; Yamanami, Masashi; Tsukimura, Takahiro; Togawa, Tadayasu; Sakuraba, Hitoshi; Gojo, Satoshi
Cell transplantation is expected to be another strategy to treat lysosomal diseases, having several advantages compared to enzyme replacement therapy, such as continuous enzyme secretion and one-time treatment to cure diseases. However, cell transplantation for lysosomal diseases holds issues to be resolved for the clinical field. In this study, we developed a new ex vivo gene therapy platform using a transplant pack, which consists of a porous membrane made of ethylene-vinyl alcohol in the pack-type and spheroids with scaffolds. These membranes have countless pores of less than 0.1 µm 2 capable of secreting proteins, including alpha-galactosidase enzyme, and segregating the contents from the host immune system. When the packs were subcutaneously transplanted into the backs of green fluorescent protein (GFP) mice, no GFP-positive cells migrated to the transplanted pack in either autogenic or allogenic mice. The transplanted cells in the pack survived for 28 days after transplantation. When cells overexpressing alpha-galactosidase were used as donor cells for the packs and implanted into Fabry disease model mice, the accumulation of the alpha-galactosidase enzyme was also observed in the livers. In this study, we reported a new ex vivo therapeutic strategy combining macroencapsulation and cellular spheroids with scaffolds. This pack, macroencapsulated spheroids with scaffolds, can also be applied to other types of lysosomal diseases by modifying genes of interest.